2021
DOI: 10.1111/acv.12732
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in plain sight: risk mitigation by a cryptic carnivore foraging at the urban edge

Abstract: As natural habitat is progressively transformed, effective wildlife conservation relies on understanding the phenotypic traits that allow select species to persist outside of protected areas. Through behavioural flexibility such species may trade off abundant resources with risks, both real and perceived. As highly adaptable mesocarnivores, caracals (Caracal caracal) provide an opportunity to examine development of successful foraging strategies in high‐risk developed areas. Here we investigated caracal resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 95 publications
(124 reference statements)
4
25
0
Order By: Relevance
“…We hypothesized that raccoon dogs and Japanese badgers would shift their temporal activity patterns to be more diurnal when released from competitive pressures of humans due to COVID‐19 restrictions. Mesocarnivores (small‐ to mid‐sized carnivore species) are known to shift their temporal patterns depending on a variety of factors and are often completely nocturnal in urban areas (avoidance of dominant carnivores: Frey et al, 2022 ; Suraci et al, 2021 ; Wang et al, 2015 ; avoidance of humans: Gaynor et al, 2018 ; Riley et al, 2003 ; Tigas et al, 2002 ; prey activity: Leighton et al, 2021 ). We found that raccoon dogs became more diurnal during their foraging behavior with substantial shifts in their activity patterns in 2020, while Japanese badgers exhibited diurnal foraging behavior in 2020 after never exhibiting it in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that raccoon dogs and Japanese badgers would shift their temporal activity patterns to be more diurnal when released from competitive pressures of humans due to COVID‐19 restrictions. Mesocarnivores (small‐ to mid‐sized carnivore species) are known to shift their temporal patterns depending on a variety of factors and are often completely nocturnal in urban areas (avoidance of dominant carnivores: Frey et al, 2022 ; Suraci et al, 2021 ; Wang et al, 2015 ; avoidance of humans: Gaynor et al, 2018 ; Riley et al, 2003 ; Tigas et al, 2002 ; prey activity: Leighton et al, 2021 ). We found that raccoon dogs became more diurnal during their foraging behavior with substantial shifts in their activity patterns in 2020, while Japanese badgers exhibited diurnal foraging behavior in 2020 after never exhibiting it in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Next, using data provided under agreements from both Eskom and the City of Cape Town, we calculated the average electrical transformer density and human population density (see Table S2 for landscape covariate information). We calculated 95% LoCoH-a (adaptive) home ranges for animals for which we had a minimum of 30 days of three-hour fix interval movement data (Getz et al 2007) implemented in t-locoh (Lyons et al 2013) as in Leighton et al 2021. For opportunistically sampled caracals (n=31), we calculated these spatial variables within a circular buffer around the GPS location where the animal was found.…”
Section: Measuring Caracal Landscape Usementioning
confidence: 99%
“…Around the rapidly expanding city of Cape Town, South Africa, caracals (Caracal caracal) selectively forage at the urban edge (Leighton et al 2021) but unwittingly experience pollutant…”
Section: Introductionmentioning
confidence: 99%
“…Our study has provided the first report of urban landscape use by fishing cats, indicating they could be among the felid species that can adapt to a life within cities, rather than remaining at the urban-wildland interface (Leighton et al 2021;Riley et al 2003Riley et al , 2014. While other urban felid studies report human population densities in their study areas, ranging from 471.6 people/km 2 (Texas, USA; Lombardi et al 2017) to 1687.0 people/km 2 (California, USA; Markovchick-Nicholls et al 2008), the human population density in Colombo is 2.1-7.6 times greater (3608 people/km 2 ; Central Bank of Sri Lanka 2019).…”
mentioning
confidence: 92%
“…Data download was attempted at a weekly cadence. All collars weighed < 5% of each individual's total body weight, as recommended by other studies (Kenward 2000), and once recovered from immobilisation, all individuals were immediately released into their respective sites.…”
mentioning
confidence: 99%